Microelectronic Applications of Chemical Mechanical Planarization 2007
DOI: 10.1002/9780470180907.ch20
|View full text |Cite
|
Sign up to set email alerts
|

CMP—The Next Fifteen Years

Abstract: In the early 1990s, reports by some IC manufacturers on the use of silicon wafer polishers to reduce the topography in interlevel dielectric (ILD) films created by multiple levels of metallization began to surface. Dismissed at first as irrational, such reports eventually proved to be true as the CMP industry began gaining ground. By the end of the decade, feature densities approaching sub-100 nm demanded not only an ILD CMP but CMP steps in the front end of the line (FEOL) as well. Process designers referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Semiconductor processing technology has led to decreased transistor sizes and an increased number of integrated transistors, resulting in highly integrated semiconductor devices with high performance [1,2]. To integrate more devices, a multilevel interconnection structure is essential, and a surface planarization process is required for the stable deposition of the layers [3].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor processing technology has led to decreased transistor sizes and an increased number of integrated transistors, resulting in highly integrated semiconductor devices with high performance [1,2]. To integrate more devices, a multilevel interconnection structure is essential, and a surface planarization process is required for the stable deposition of the layers [3].…”
Section: Introductionmentioning
confidence: 99%
“…Later, this technology was also applied to the semiconductor device manufacturing process. [2][3][4][5] CMP technology has now made it possible to achieve flat and smooth surfaces at the nano-or atomic level. On the other hand, CMP faces many challenges such as: (1) Reducing nano-level defects and contamination, (2) Polishing of a wide variety of difficult-to-process materials, from hard brittle materials to composite materials, and (3) Improving productivity through highly efficient polishing.…”
mentioning
confidence: 99%
“…The abrasive particles come to remove this layer of transformed matter. Joseph et al [1] define three main players in this process, shown in figure 1, presented by: 1. The surface to be polished.…”
Section: Introductionmentioning
confidence: 99%